Efficacy of Some Botanical Powders as Grain Protectants Against Pulse Beetle (Callosobruchus chinensis L.) on Ricebean (Vigna umbellata Thunb.) - Kuotsu, Khrieketou; Neog, Pankaj (International Journal of Bio-resource and Stress Management, 2022)
An experiment was conducted during January−June of 2019 and 2020 in the laboratory of the Department of Entomology, School of Agricultural Sciences and Rural Development, Nagaland University, Medziphema Campus, Dimpaur district, Nagaland, India to evaluate the efficacy of some botanical powders as grain protectants against pulse beetle, Callosobruchus chinensis (L.) on ricebean, Vigna umbellata (Thunb.). The experiment was conducted in a Completely Randomized Design (CRD) with 3 replications. A total of 7 plant materials viz., Azadirachta indica, Piper nigrum, Ocimum tenuiflorum, Eucalyptus globules, Allium sativum, Pongamia pinnata and Litsea citrata were evaluated for their effect on oviposition reduction, adult emergence, infestation and weight loss by C. chinensis. All the plant products were mixed with susceptible ricebean seeds @ 5% w/w, Malathion 5% dust @ 1% w/w was used as standard check and untreated seed was used as control. Among the botanical powder treatments, the highest reduction in oviposition was found in L. citrata followed by A. indica and P. nigrum. The % adult emergence was also lowest in L. citrata treatment (55.23%) compared to the other botanical treatments. L. citrata seed powder also provided effective protection up to 2 months of storage with an infestation of 16.12% and weight loss of 2.40%, respectively followed by P. nigrum seed powder with an infestation of 31.67% and weight loss of 6.93%, respectively. The least effective was found in P. pinnata leaf powder. The findings revealed the potential of L. citrata and P. nigrum as grain protectants against pulse beetle in storage.